GW24-e3737 MicroRNA-210 mediates the protective effect of nitrate on endothelial progenitor cells against senescence induced by angiotensin II through suppressing gene SCH9. (1st October 2013) - Jianfeng, Xu; Juying, Qian; Li, Lin; Yanhua, Gao; Li, Shen; Mingqiang, Fu; Yunzeng, Zou; Aijun, Sun; Dadong, Zhang; Junbo, Ge
Abstract : Objectives: To examine a hypothesis that organic nitrate, widely used to treat vascular contraction, protects endothelial progenitor cells (EPCs) against senescence induced by angiotensinII (AngII); and if so, to investigate the underlying mechanisms involved. Methods: Human-derived EPCs, treated with PBS or nitrate (100 μmol/L), was subsequently exposed to AngII (100 nmol/L) for 24 hours in vitro . The senescence-associated β-galactosidase test and the detection of p16 Ink4a /p19 Arf expression were used to evaluate the cellular senescence. The miRNAs transcriptome was analysed by microarray and was verified by real-time PCR. The gain- and loss-of-function methods through lentivirus infection were administrated to evaluate the role of miRs in the senescence of EPCs induced by angiotensinII. Additionally, a luciferase reporter assay was performed to confirm associations between miRNAs and their putative targets, which was furthermore verified by small interference RNA (siRNA) and Western-blot. Results: AngII significantly induced EPCs senescence while nitrate not. However, the effect of AngII on cellular senescence could be statistically attenuated by nitrate pre-culture, indicated as the differences in the percentage of senescent EPCs between AngII group and pre-culture group [(72.6 ± 6.92)% vs. (43.7 ± 7.55)%, P <0.05], as well as the expressions of p16 Ink4a (3.56 ± 0.76 vs. 1.93 ± 0.42, P <0.05) and p19 Arf (4.88 ± 0.72 vs. 2.67 ± 0.54, P <0.05). MiR-210 in pre-culture group was discovered to up-regulate more over 4 times than that in AngII group ( P <0.05). Moreover, forced expression of miR-210 in EPCs, compared with scramble over-expression, was evidenced to dramatically reverse cell senescence induced by AngII [(37.6 ± 7.43)% vs. (71.8 ± 6.63)%, P <0.05] and drastically decrease both p16 Ink4a and p19 Arf expressions (both P <0.05). In contrast, suppression of miR-210 in EPCs, raising putative miR-target SCH9 expression, statistically abolished the protective effect of nitrate on EPCs senescence [anti-miR group vs. null group: (72.6 ± 6.92)% vs. (45.8 ± 8.39)%, P <0.05]. Most importantly, the phenotypic changes were discovered to be recovered by SCH9 knockdown ( P <0.05). Conclusions: Nitrate protects EPCs, mediated by miR-210 up-regulation and SCH9 suppression, against cellular senescence induced by AngII, which is of a crucial significance for those rennin-dependent hypertensive patients with vascular injury.